Obeid's contribution Slave markets In the Umayyad economy, - kechida, Ridha; ouled madhi, rabeh (Journal of Social Sciences and Humanities, 2020)
This research includes the study of the slave markets in the Islamic Orient, the time of the construction of a umayyad, because it is of great importance in the economic system, especially in its effects on the social and political structure, including the pattern of consumption and living, and it also dictates the relations between the Levant region. In the context of social relations between the various actors within the markets, all social classes, Muslims and others, meet and talk, and in which the various elements of the population of Arabs, Arabs, Muslims and people of Dhimma are mixed. The market was a center of political life where people converged under the guise of trade, away from the eyes of the sergeants of governors and rulers, plotting plots and sire In addition to the economic, social and political dimension, we are able to study the markets to identify the role of these markets in the emergence of villages and cities, some of which have been transformed into a commercial center, and with the growth and prosperity of these cities emit other activities such as the development of architecture and its arts, and the development of culture and its creations, and these cities may turn Trade from economic centers to centersof political influence, this can be identified by studying the markets and their importance in the Umayyad state in the Islamic Orient The political stability in the Umayyad state has had a great impact in the markets and in the activity of economic life, as it opened the door to work in it and attracted the labor force to it, and they were active in their agriculture to meet their food and food needs, as well as the movement of internal trade, as well as the movement of internal trade., Among these markets we find the slave markets or slave markets, and that is why we tried to highlight the contribution of slave markets to the Umayyad economy (41H-132H), and to explain this economic contribution we divided our study into three elements we addressed in the first: a brief history of slaves, in which we addressed: the definition of slaves and so on: Their markets, the second element was the slave markets in the Islamic State and in the third element the contributions of slaves in grazing and agriculture and their contributions to manufactures and crafts and their contributions in the field of trade, and accordingly we have extrapolated various sources and references to reach the desired result .